Patterns of Digital Misconduct: A Survey of Cyberbullying Behaviors in a High School Setting - Raikhola, Pushkar Singh (International Journal of Atharva, 2025)
This study examined the patterns of cyberbullying among high-school students using a quantitative, questionnaire-based survey design. Conducted at Geetanjali Secondary Higher School/College, the study targeted students aged 18 to 20 years, with a total of 201 respondents participating voluntarily through a Google Form questionnaire. The findings revealed that while the majority of students did not engage in direct cyberbullying behaviors, a significant minority admitted to various forms of online misconduct. For instance, 7% of respondents reported often stealing personal information, while 10.5% admitted to frequently stealing computer nicknames. Similarly, 7.5% reported always threatening others online, and 9.5% sometimes insulted peers in online forums. Subtler behaviors such as exclusion blocking or removing comments were reported by 13.4% of respondents, while 9% acknowledged sometimes sharing private conversations without consent. Mocking others’ online comments was also relatively common, with 14.9% admitting to doing so sometimes. Severe behaviors such as sending threatening emails (11.5% sometimes) and stealing email access (10.6% rarely) were less frequent but still present. Overall, the results suggest that while cyberbullying is not a dominant practice among the surveyed students, a considerable portion of participants engage in harmful online behaviors at varying levels.